A regularized non-smooth contact dynamics approach for architectural masonry structures. (15th July 2017) - Beatini, Valentina; Royer-Carfagni, Gianni; Tasora, Alessandro
Highlights: A non-smooth contact dynamic approach has been implemented to analyze masonry blocks under dry friction. Relying upon the theory of measure differential inclusion, the problem is set as a cone complementary problem. Custom tools within a user-friendly parametric design software allow pre-processing and post-processing. The influence of the bond pattern on the ultimate static load of masonry block assemblies is studied in paradigmatic examples. Oscillating movements of the ground can diminish the stabilizing effects of friction due to local collisions. Abstract: A Non-Smooth Contact Dynamic (NSCD) formulation is used to analyze complex assemblies of rigid blocks, representative of real masonry structures. A model of associative friction sliding is proposed, expressed through a Differential Variational Inequality (DVI) formulation, relying upon the theory of Measure Differential Inclusion (MDI). A regularization is used in order to select a unique solution and to avoid problems of indeterminacy in redundant contacts. This approach, complemented with an optimized collision detection algorithm for convex contacts, results to be reliable for dynamic analyses of masonry structures under static and dynamic loads. The approach is comprehensive, since we implement a custom NSCD simulator based on the Project Chrono C++ framework, and we design custom tools for pre- and post-processing through a user-friendly parametric design software. Representative examples confirm that the method can handle 3-D complex structures, as typically are architectural masonry constructions, under both static and dynamic loading.